Exposure of Portuguese population to mycoestrogens: a public health concern? - Martins, Carla (2020)
Alternariol (AOH) and zearalenone (ZEN) are mycotoxins that occur widely in food commodities, with particular incidence in cereals [1,2]. Both mycotoxins present estrogenic effects, therefore, it is crucial to assess the human exposure and the associated risk [2,3]. To date, there is a lack of human studies to assess exposure to ZEN and AOH through biomarkers analysis in Portugal. In the scope of the National Food, Nutrition, and Physical Activity Survey of the Portuguese General Population (IAN-AF, 2015-2016), 94 participants collected 24h-urine samples [4]. Following a salt-assisted matrix extraction, urine samples were analyzed by liquid chromatography–mass spectrometry (LC-MS/MS) for the simultaneous determination of ZEN, α-zearalenol (α-ZEL), β -zearalenol (β-ZEL), α-zearalanol (α-ZAL), β-zearalanol (β-ZAL), zearalanone (ZAN), zearalenone-14-glucoside (ZEN-14-GlcA), α-zearalenol-glucoside (α-ZEL-GlcA), β-zearalenolglucoside (β-ZEL-GlcA), zearalenone-14-sulfate (ZEN-14-Sulf), alternariol monomethyl ether (AME) and AOH. Risk characterization was performed using the Hazard Quotient (HQ) approach. ZEN, ZEN-14-GlcA and AOH were detected in 48%, 16% and 29% of analyzed samples, respectively, and median levels were 0.17 μg/L for ZEN and ZEN-14-GlcA and 0.28 μg/L for AOH. Participants were exposed to ZEN (n=35), AOH (n=15) and some volunteers showed co-exposure to both mycotoxins (n=12). Risk characterization of exposure to ZEN was performed and 24% of participants presented a HQ > 1, thus exceeding the Tolerable Daily Intake (TDI) of 0.250 μg/kg bw/day. There is no toxicological data available to support the establishment of a TDI for AOH, thus the risk associated with this toxin was not characterized [2,5]. The present study generated, for the first time and within a human biomonitoring study, reliable data regarding the exposure of the Portuguese population to ZEN and AOH. These data are crucial to perform a more realistic risk assessment, contributing to more effective preventive measures for health protection of the Portuguese population.